A convergent total synthesis of ouabagenin1. Issue 6 (18th June 2015) - Mukai, Ken; Kasuya, Satoshi; Nakagawa, Yuki; Urabe, Daisuke; Inoue, Masayuki
<x xml:space="preserve">Abstract</x> A convergent total synthesis of ouabagenin, an aglycon of cardenolide glycoside ouabain, was achieved by assembly of the AB-ring, D-ring and butenolide moieties.